Terpaan Berita Perceraian di Media Sosial terhadap Keputusan Menunda Pernikahan Dewasa Awal - Vidia Viddari Ruzan (Sadida Islamic Communications and Media Studies, 2024)
This study aims to determine the influence of exposure to divorce news on social media on the decision to postpone marriage in early adulthood in Banda Aceh City, the rapid development of information technology and social media that affects various aspects of life, including marriage. The approach used in this study is a quantitative descriptive approach with a survey method using a questionnaire that assesses the frequency, duration, and attention of Instagram users to divorce news. The population of this study is the early adulthood of Banda Aceh City as many as 82,963 people with the number of samples taken amounting to 100 people who have been determined using the Slovin formula with a simple random sampling technique. The results of the study showed that there was a significant influence of frequency, duration, and attention exposure to divorce news on Instagram on the decision to postpone marriage in early adulthood in Banda Aceh City. This research is expected to contribute to the study of mass communication, especially related to the effect of social media on people's social behavior.